A Study on the Role of Family in the Academic Achievement of Secondary School Students - V, Sini.; Kumar, Anil; B, Muhammed Anas. (International Journal of Atharva, 2025)
Family plays a crucial role in shaping the academic achievement of secondary school students. This study investigates the impact of family acceptance on education and its correlation with students' academic performance, focusing on secondary school students in the Thiruvananthapuram district. Using a normative survey method, data were collected from 305 students through standardized tools, including a Family Acceptance Education Rating Scale and an achievement test in Malayalam. The study employed stratified sampling and analyzed the data using statistical techniques such as Pearson’s product-moment correlation and tests of significance. The findings reveal a significant positive correlation between family acceptance of education and academic achievement, particularly among boys, girls, rural students, and private school students. However, this relationship was not significant for urban and government school students, suggesting contextual influences on the role of family support. The study highlights that families act as primary scaffolders, providing emotional, social, and academic support that fosters self-efficacy, resilience, and a positive attitude toward learning. The results underscore the importance of familial involvement in education, especially during adolescence, a critical period for academic and personal development. The study concludes that family acceptance significantly influences students' academic outcomes and recommends strengthening family-school partnerships to enhance educational achievement. Policymakers and educators should prioritize initiatives that encourage parental involvement and create supportive home environments to maximize students' potential.